Peruntukan dan pemakaian keterangan dalam kes-kes kehartaan di Indonesia: Analisis dari sudut keterangan Islam / Hidayat Muhammad - Hidayat , Muhammad (2016)
Allah SWT the Judge of Judges is Most Judicious. As guidance to mankind in safeguarding all their wordly matters and dealing, Allah has sent down His Divine Law (Shariah) through His Prophets and Messengers. All existing laws, even though drafted by human being but with the intention to benefit mankind, are considered as Syariat of Allah. In order to conduct hearings for disputes within Muslim families in Indonesia, due to lack of legislation for self-evidence, Islamic Court (Peradilan Agama) which has jurisdiction over such matter had to applied evidence laws of Civil Court inherited from the colonials. Over than 150 years, Indonesian Civil Code (KUHP), HIR and RBG have been applied as a source of primary laws in Indonesian Court until now (writing this Thesis ) there is no initiative yet to improve it especially on law of evidence. It’s because making of human been, no guaranteed to tell that there are not mistakes in all those laws. In order to identify these laws, Researcher has to identify and study on how compatible are they with the meaning of Islamic evidence. This is important, in order to identify any shortcoming that may exist whether There is a shortage in it both in terms of legislation or its impact in solving the case for the betterment of such laws. However, this study only involving Muslim properties including cases of Inheritance, Wills, Gift and Endowments.According to Ibn al-Qayyim, Whatever of evidence that may disclose the justice is received. Therefore, interpretation on the law of evidence by judge strongly influence how far of evidence which was not mentioned in the legislation could be used by judges. This is because, in the property cases, evidence that used as listed by law is more less than criminal cases. In order to achieve this objective, few methodologies can be used such as scurutinising and analyzing of existing laws, go on to ensure that they are compatible with the books written by Islamic Scholars (Ulama). After going through such analysis, Researcher concludes that even if the laws are not contradicting with the Shariah law, there is still a need for a more thorough study so as to ensure its relevance to date, there is still so much more to be done.